The global burden of colorectal cancer attributable to high body-mass index in 204 countries and territories: findings from 1990 to 2021 and predictions to 2035 - Jin, Xiaoqian; Dong, Danfeng; Xu, Zixuan; Sun, Mingming (Frontiers in Nutrition, 2024)
Background The association between high body-mass index (BMI) and colorectal cancer (CRC) has been confirmed and gained attention. However, a detailed understanding of the disease burden of high BMI and CRC remains lacking. Objective This study aimed to assess the temporal and geographical trends of CRC deaths and disability-adjusted life years (DALYs) caused by high BMI globally from 1990 to 2021, providing effective guidance for developing prevention and treatment strategies. Methods We used data from the 2021 Global Burden of Disease study to assess the global, regional, and national Deaths, DALYs, age-standardized mortality rate (ASMR), and age-standardized DALY rates (ASDR) caused by CRC related to high BMI, and further calculated the estimated annual percentage change (EAPC). We also considered factors such as gender, age, and sociodemographic index (SDI). We explore the relationship between EAPC and ASMR/ASDR (1990) and between EAPC and SDI (2021). Further, the autoregressive integrated moving average (ARIMA) model was applied to predict the disease burden from 2022 to 2035. The risk factors were calculated by Population Attributable Fraction (PAF). Results In 2021, CRC caused by high BMI resulted in 99,268 deaths (95% Uncertainty Interval (UI): 42,956–157,949) and 2,364,664 DALYs (95% UI: 1,021,594–3,752,340) globally, with ASMR and ASDR being 1.17 per 100,000 population (95% UI: 0.51–1.87) and 27.33 per 100,000 population (95% UI: 11.8–43.37), respectively. The disease burden was higher in males and the elderly, with significant differences between regions and sociodemographic groups. From 1990 to 2021, the ASMR for CRC associated with high BMI revealed little change globally, while the ASDR revealed an upward trend. The burden of CRC caused by high BMI has shifted from high SDI regions to low and low-middle SDI regions. Additionally, from 2022 to 2035, ASMR and ASDR are expected to increase in males, while ASMR and ASDR in females are expected to remain relatively stable. Conclusion From 1990 to 2021, the number of deaths and DALYs related to high BMI-associated CRC globally, as well as ASMR and ASDR, continue to rise. We predict that ASMR and ASDR may further increase by 2035, making it crucial to take timely and targeted interventions.